When A Fully D-Stable Module is Quasi-Projective - Abbas, M.S; Al-Hosainy, A. M. A (Journal of Asian Scientific Research, 2014)
The concept of full d-stability of modules was introduced by the authors in a previous paper. It is stronger than the duo property. Although quasi-projectivity is not a necessary condition for full dstability, it is inherent with this property in most of the known examples in such a way that it was difficult to give an example of a fully d-stable module which is not quasi-projective. This motivates the subject of this paper.